CO-INFECTION OF NEWCASTLE DISEASE, COCCIDIOSIS, AND COLISEPTICEMIA IN BROILER CHICKEN: CASE STUDY - Adi Setiawan; Tjokorda Sari Nindhia; Ida Bagus Made Oka; Yeocelin Meida Utami; I Made Kardena (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Newcastle disease (ND), coccidiosis, and colisepticemia are major infectious diseases in broiler chickens that can lead to high economic losses due to increased morbidity and mortality. The subject of this case study is a 28-day-old broiler chickens from one of the closed house farms in Pering Village, Blahbatuh District, Gianyar Regency, Bali. This case study aims to establish a diagnosis based on medical history, epidemiological data, clinical symptoms, anatomical pathology, histopathology, and laboratory test results. Clinical symptoms of the affected chickens included subcutaneous emphysema, feather loss covering nearly two-thirds of the abdominal and chest areas, feather loss, decreased appetite over the past four days, sneezing, watery diarrhea mixed with green and white mucus, blackened comb tips, and clear yellow exudate from the nasal cavity. Epidemiological survey results showed a morbidity rate of 2.6%, a mortality rate of 1.8%, and a case fatality rate (CFR) of 71%. Pathological anatomy examination results indicated that nearly all organs showed hemorrhage, with some organs exhibiting enlargement, white spots, and soft consistency. Similar findings were observed in histopathology, with nearly all organs showing inflammatory changes characterized by lymphocyte, neutrophil, macrophage infiltration, hemorrhage, necrosis, and edema. Hemagglutination (HA) testing showed a titer of 23 HAU, while hemagglutination inhibition (HI) testing was confirmed the presence of ND virus. Bacterial culture result of organ samples using Eosin Methylene Blue Agar (EMBA) medium was positive result for Escherichia coli, and fecal examination identified Eimeria spp. Therefore, it was concluded that the infected chickens were diagnosed with Newcastle disease, coccidiosis, and colisepticemia. These multiple infections contributed to the severity of clinical signs and high case fatality, highlighting the need for effective prevention and biosecurity measures.